(untitled) (Journal of the College of Basic Education, 2025)
This research aims to study the transformation in understanding the relationship between temporal meaning and verb in classical and modern Arabic grammar, by tracing the historical development of the concept of time in the Arabic language. The study adopts an analytical-historical approach, relying on classical and contemporary grammatical sources (Sibawayhi, 1995), in addition to examples from spoken language taken from television programs, films, and series.The study reveals that classical Arab grammarians considered time as an internal feature of the verb: the past tense denotes past time, the present requires a context or particle to denote time, and the imperative is linked to future action (Al-Jurjani, 2003). However, modern linguists have begun re-evaluating this relationship, noting that time may not always be tied directly to the verb form, but rather influenced by other factors such as context, temporal particles, aspect, and the function of the sentence.Moreover, the field study showed that spoken language reflects clear changes in the use of tense, making it an essential source for understanding how the relationship between verb and time evolves in everyday communication.